EVALUATION OF AXILLARY RESPONSE TO NEOADJUVANT CHEMOTHERAPY IN LUMINAL BREAST CARCINOMA TREATED IN CAISM: UNICAMP BETWEEN 2013 AND 2018 - Moreira, Pedro Lavigne de Castello Branco; Santos, César Cabello dos; Torresan, Renato Zocchio; Brenelli, Fabrício Palermo; Ramalho, Susana Oliveira Botelho (Mastology, 2020)
Introduction: Breast cancer is the most common malignant neoplasm affecting the female gender (besides non-mela-noma skin cancer). It is a heterogenous disease with different phenotypic subtypes; the most common subtype is the luminal-like, which presents poor response to neoadjuvant chemotherapy. If patients with positive axilla at diagnosis are submitted to surgery, axillary dissection must be carried out, which is a surgery with major morbidities; however, if the patients are treated with neoadjuvant chemotherapy and develop negative axillary disease, they can avoid axillary dis-section. Objective: to assess axillary response to neoadjuvant therapy in patients with cT1-3 cN1-2 luminal-like breast cancer. The secondary objectives were to assess the association between the axillary response to neoadjuvant chemo-therapy according to: tumor replication marker (Ki67), estrogen and progesterone receptors (ER and PR), tumor histolo-gical grade, according to the Nottingham classification, tumor size (cT), level of axillary compromise (cN1, cN2 or cN3), chemotherapy scheme, luminal subtype and epidemiological variables (age, BMI, menopause status). Method: reconsti-tuted cohort including female patients diagnosed with invasive breast cancer stage cT1-3 cN1-2 M0 at physical or ultra-sound examination, who received neoadjuvant chemotherapy. Axillary compromise can be assumed. The patients were followed-up at the ambulatory of Clinical Oncology and Mastology at CAISM UNICAMP. A convenience sample was used. Statistical analysis: Statistical analysis will be carried out using the Statistical Package for the Social Sciences, version 22.0 (SPSS). Correlations between categorical variables will be analyzed with the chi-square test. Differences between means will be verified using Student’s t-test. Nonparametric tests will be used according to necessity. All tests will be bicaudal, with 5% as the threshold of statistical significance. Results: One hundred and forty three cases were included, respecting the inclusion criteria. Of these, 2.8% evolved with pathological complete response per se (pCR); 5.6%, with pCR in the breast; and 23.1%, with axillary pCR. The lower the axillary compromise at diagnosis, the higher the frequency of axillary pCR (cN1 26.7%, cN2-3 11.1% - p=0.049). The smaller the residual lesion in the breast after chemotherapy (ycT), the higher the chances of axillary pCR (ycT0 28.8%, ycT1 38.5%, ycT2 9.7%, ycT3-4 0 cases – p=0.042). The anthropometric, immunohistochemical and anatomopathological parameters did not present statistical relevance. Conclusion: Patients with luminal-like breast cancer and axillary compromise at diagnosis may benefit from avoiding dissection in about 20% of the time if treated with neoadjuvant chemotherapy, so this therapeutic strategy should be considered in these cases.